Designing orodispersible films containing everolimus for enhanced compliance and bioavailability. (2nd October 2020) - Ma, Yidi; Guan, Rou; Gao, Shuying; Song, Wei; Liu, Yubo; Yang, Yang; Liu, Hongzhuo
ABSTRACT: Introduction: Everolimus (EVR) has been approved for the treatment of various advanced cancers and its indications are increasingly expanding. Therefore, it is crucial for patients who have difficulty in swallowing, such as pediatric and elderly patients, to obtain a convenient formulation. The oral absorption of EVR is limited due to its low solubility in water, intestinal metabolism by CYP3A4 enzyme, P-gp-mediated efflux, and metabolism in the liver. The aim of this study was to develop a novel sublingual orodispersible film loading everolimus for improving patient compliance and enhancing oral bioavailability of EVR. Research design and methods: Sublingual orodispersible films loading EVR were prepared by the solvent casting method and evaluated by in vitro and in vivo studies. Results: The properties of films were determined by scanning electron microscopy, differential scanning calorimetry, X-ray diffraction, and Fourier-transform infrared spectrometry. The addition of acacia gum appeared to be crucial for protecting the drug from oxidation. Pharmacokinetic studies showed that loading into the sublingual orodispersible films significantly increased the oral bioavailability of EVR. Conclusion: The EVR-loaded sublingual orodispersible films are a promising, economical, and convenient approach for delivering EVR efficiently in a solid dosage form.